Resources, Motivation, and Problem Zones of the Project-Based Learning Model in Engineering Education - Bobrovskii, A. V.; Bazhutina, M. M.; Zotov, A. V.; Chizhatkina, E. D. (Vysšee obrazovanie v Rossii (Print), 2025)
This article examines the experience of implementing project-based learning in engineering education at the Center of Mechanical Engineering of Togliatti State University. The motivation of the study lies in the analysis of a model centered around a continuously operating student engineering team participating in international Formula Student competitions. The aim of the research is to identify problematic areas, their causes, and pathways for further development of this project-based learning model. A literature review revealed several types of project-based learning models used in Russian universities: models aimed at educational outcomes, such as the development of professional competencies; models focused on achieving project outcomes; product-oriented models centered on delivering tangible products for external clients; hybrid models that combine various objectives. The Togliatti State University case represents a hybrid approach, emphasizing both competency development and project outcomes. To address research questions, surveys were conducted among students, focus group discussions were held with student leaders, and interviews were carried out with project advisors and employers. Key findings include positive evaluations from all participants regarding educational and project outcomes. At the same time the authors identified a number of challenges: predominance of external motivation among half of the students; shortage of supervisors and allocated instructional hours for projects, leading to limited individual engagement with teams; inability to diversify the model’s scope and content solely through existing resources. The study suggests solutions such as further individualization and diversification of project   based learning by involving more student leaders, expanding case studies, and engaging consultants from industry partners.